Dispute Resolution Through Online Mediation Based on Supreme Court Regulations - Hidayati Fitri; Khairani Khairani; Roni Efendi (Alfuad: Jurnal Sosial Keagamaan, 2024)
This article is motivated by the need for mediation to be carried out optimally to resolve cases in court. The purpose of this article is to explain the substance of mediation in the process of resolving divorce cases and the importance of mediation in resolving household disputes. The method used in this paper is the Normative method with a conceptual approach to analyze problem-solving from the aspects of legal concepts and values contained in norms. The data collection technique used in this paper is a documentation technique and the results are analyzed qualitatively. The research results show that the mediation regulations contained in PERMA which regulate mediation contain important substances that must be understood by the mediator and both parties. Mediation is important to carry out directly to minimize the occurrence of divorce and minimize disputes that may arise after the divorce occurs.